Simulation of costs and benefits of supplementing milking cows with legumes during the dry season in two hillside regions of Nicaragua - Holmann, Federico J.; Tiemann, Tassilo T. (2008)
Objectives of this study were to compare costs and expected benefits of feed supplementation in cattle with alternative shrub legumes during the dry season using as a case study the hillsides of Central Nicaragua. The information used was gathered in a survey of 32 farms in the states of Boaco and Chontales in Central Nicaragua. The survey was designed to determine herd structure, land use patterns, milk and beef production, and use of inputs for animal nutrition, in order to estimate production, reproductive parameters and employment of family/contracted labor, as well as indicators of profitability of the alternatives under study. To calculate the economic return to the investment in alternative forages, a simulation model that applies optimization techniques through linear programming, implemented as a spreadsheet, was used to perform an ex ante evaluation of the costs and benefits of different land use alternatives and of interactions between technological components and biological productivity. The model compares the costs and benefits of the traditional feeding system versus an improved feeding system.